Does no-intraoperative correction of chin deviation prevent costochondral graft overgrowth in pediatric temporomandibular joint ankylosis management - an intermediate outcome study - Poonam Yadav; Ajoy Roychoudhury; Ongkila Bhutia; Kamalpreet Kaur; Rajiv Balachandran (Journal of Oral Biology and Craniofacial Research)
The use of costochondral graft is controversial for pediatric temporomandibular joint reconstruction due to its unpredictable growth. The height of the cartilage is directly responsible for the growth capacity of costochondral graft. Even after keeping the cartilage in costochondral graft to a recommended height, overgrowth has been reported. Traditionally during costochondral graft fixation, chin deviation is corrected intraoperatively. The investigators hypothesized that this intraoperative manipulation of mandible to correct chin deviation and maintaining the chin in new position causes excessive stress and strain in the muscular functional matrix. The authors believe that this may be the reason for excessive growth trigger on the grafted side. This study intends to prove the hypothesis of no-intraoperative correction of chin deviation can prevent overgrowth of the costochondral graft. We implied this technique in pediatric temporomandibular joint ankylosis patients managed with osteoarthrectomy and reconstructed with costochondral graft. Patients with at least a follow-up of 30-months were included in the study. The study sample consisted of 20 patients. All the patients had adequate growth with improvement in facial asymmetry. The results of the present study supports our hypothesis of no-intraoperative correction of chin deviation as a technique to prevent overgrowth of costochondral graft. We recommend this technique to allow catch-up of growth rather than acceleration of growth. This change in technique needs more research, randomized controlled trial for reliability and long-term results.